Prática social docente: para além das primeiras aproximações da pedagogia histórico-crítica - Prado, Jeovandir Campos do (2017)
This thesis aims to promote a discussion about the (social and pedagogical) teaching practice required in Historical-Critical Pedagogy and its relation with the method of Marxian analysis. It is also intended to problematize a teaching action, at the same time, coherent with the Marxist aspirations and the pedagogical theory of Dermeval Saviani, considering that a pedagogical theory based on historical and dialectical materialism presupposes embedded a specific form of treatment of multiple Social phenomena. In this direction, we first sought to analyze the foundations and the theoretical-methodological basis of Historical-Critical Pedagogy, its connection with Marxist theory and, in it, the role of social practice within. Next, the social practice category in Marxism was explored in order to understand Saviani's meaning of this important category in his pedagogical method. Finally, in the light of these referrals, emphasis was placed on the specificity of social practice in seeking to emphasize a teaching action better identified with Savinian theory and also with Marxist thought, that is, from a historical-critical perspective. The methodological path chosen included bibliographical research, documentary analysis and literature analysis linked to the theme, however, without giving up the dialectical treatment that allows understanding the movement of reality in its organicity and complexity. It was concluded at last that the Historical-Critical Pedagogy, as a pedagogical instrument of struggle, brings in its essence, lucidity and combativity that are fundamental for a safe awareness of the educational praxis within the capitalist school. But this possibility is conditioned to a "conscious unity" between theory (Marxism, education and pedagogy) and practice (teaching action based on the objectives of the theory) without which it will be difficult to achieve.